PBL in an EAP classroom: an insight study on students' language skills / Zuriani Yaacob - Yaacob, Zuriani (2012)
Current language teaching methodologies and recent educational changes in Malaysia have exposed the students to independent or autonomous learning style. In Malaysia, Problem-based Learning (PBL) is gaining popularity and the acceptance among academicians and students has led to its successful implementation (Abu Hassan et aI., 2004). Hence, the objective of the study was to explore students' perceptions and attitude towards the implementation of PBL curriculum instruction in an EAP normal setting classroom. It also aimed to increase understanding of the PBL effectiveness on learners' communication skills, vocabulary knowledge, and writing performance. In language classrooms, PBL is believed to create a conducive environment for the language skills to grow (Steinemann, 2003) . This is significant in suggesting that communication skills, vocabulary, analytical and critical thinking abilities are better acquired in PBL setting than in traditional classrooms (Zamnah, 2005). This study adopted a predominantly quantitative approach in which the data was later corroborated by qualitative approach to ensure the validity of the data collected. The collaborative problem-solving process within an EAP classroom was observed as a case study. The population of this study comprised of first semester students of Asasi Undang-Undang (Law Foundation Programme) from a local government university i.e. Universiti Teknologi Mara (UiTM) Kuantan City Campus in Pahang. The study utilized multiple sources of evidence including pretest and posttest, direct observations, presentation assessments, reflective journals, semi-structured interviews and questionnaire based suryey to enable triangulation of the data. The findings of this study indicated that the students had positive attitude towards learning second language through Problem-based Learning (PBL) instruction. On top of that, it was evident that PBL was effective in developing the students' communication skills, vocabulary, and writing skills through PBL approach. These results were consistent with previous research indicating that the implementation of PBL in language learning process significantly increased the students' language and generic skills. In terms of pedagogical implications, it was evident that students need to be exposed more to the use of PBL to minimize their dependency on class instructors. Giving the students opportunities for self-directed learning will promote positive changes in their effort of learning English as a second language. Besides, in promoting such independent learning environment, it is important for the facilitator to clarify about PBL, its underlying principles and characteristics in which later would enable them to become familiar with the PBL processes. Effective communication during PBL sessions is significant to ensure that the students feel emotionally, socially and intellectually supported. This will also be resulting in positive relationship development between the students and the facilitator.